Setting the reference for the use of Chironomus sancticaroli (Diptera: Chironomidae) as bioindicator: Ontogenetic pattern of larval head structures - Débora Rebechi; Mário Antônio Navarro-Silva (Zoologia (Curitiba), 2012)
Species of Chironomidae are widely used as bioindicators of water quality, since their larvae undergo morphological deformities when in contact with sediment contaminated with chemicals. In this work we endeavored to study the morphology of head structures (antennae, mandible, mentum, pecten epipharyngis, ventromental plate and premandible) throughout the development of the four larval instars of Chironomus sancticaroli Strixino & Strixino, 1981, which can be used in environmental impact analyses. Our results show that it is possible to differentiate among larval instars by doing a quantitative analysis on the number of striae on the ventromental plates. The six structures analyzed changed during larval ontogeny. These changes are part of the ontogeny of the immature stages not exposed to xenobiotics. We believe that the morphological pattern defined in this work can be used for comparisons with ontogenetic changes observed in field studies conducted in polluted environments.